Severe Disfiguring Scalp and Facial Oedema due to Henoch–Schönlein Purpura in a Child. (14th September 2020) - Arunath, Visvalingam; Athapathu, Arjuna Salinda; Hoole, Thabitha Jebaseeli; Aruppala, Heshan; Rathnasri, Asanka; Ranawaka, Randula; Mettananda, Sachith
Abstract : Henoch–Schönlein purpura is a small vessel vasculitis that usually presents with palpable purpura, arthritis, abdominal pain, and nephritis. Subcutaneous oedema of dependent areas is common; however, oedema in the scalp is extremely rare especially in children older than two years. Here, we report a child with massive disfiguring scalp and facial oedema due to Henoch–Schönlein purpura. An eight-year-old boy presented with characteristic palpable purpuric rash and extensive disfiguring scalp and facial swelling for five days. He complained of blurred vision, vomiting, and severe headache on the day of admission. Examination revealed an ill child with extensive oedema of the face and scalp that was tender on palpation. His blood pressure was above the 99 th percentile, and he had exaggerated deep tendon reflexes and extensor plantar responses. All biochemical investigations including renal function tests were normal. Noncontrast CT head showed normal brain, with marked soft tissue swelling of the scalp. Ultrasonography showed soft tissue oedema within and surrounding facial muscles without evidence of neck vessel compression. Urine analysis revealed microscopic haematuria on day 14 of the illness, and immunohistochemical staining of renal biopsy confirmed Henoch–Schönlein purpura nephritis. In conclusion, this case report presents a child with severe, disfiguring scalp and facial oedema due to Henoch–Schönlein purpura. It highlights that severe subcutaneous oedema of Henoch–Schönlein purpura can involve any part of the body not limiting to dependent areas.